Piglet birth weight as determining factor of optimal nutrient concentration in grower and finisher diets - Jansen van Rensburg, Christine (University of Pretoria, 2022)
Dissertation (MSc (Agric) Animal Science: Animal Nutrition)--University of Pretoria, 2021.